Analisis Keputusan Faktor Demografi Menjadi Nasabah Bank Syariah Indonesia Region Medan - Herlina Putri (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2022)
Research that has been carried out at Indonesian Islamic Banks, the problems that currently arises are that public participation is still very minimal towards Islamic banks. The purpose of this study was to determine the involvement of demographic factors of education level, income and distribution in the decision to become a customer of Bank Syariah Indonesia. In this study using qualitative research methods with data collection starting from the results of interviews, observations and documentation. Based on the results of the research that has been done, it can be seen that the demographic factor is the level of education. income and distribution have an involvement in determining the decision to become a customer of Bank Syariah Indonesia.